(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
The granulometric analysis of Bima Sandstone in Girei and environs was carried out cov ering the area within latitudes 9°16’00” and 9°24’00”N and longitude 12°28’00” and 12°38’00”E. The aim of the study is to determine the grain size distribution of the Bima Sandstone, its transportation history, and its depositional environment. Fourteen rock samples were subjected to granulometric analysis. The result shows that the sandstone is fine, medium to coarse, and very coarse-grained; it is moderate and poorly sorted. The graphic mean size ranges from −0.06Ф to 1.03Ф, which suggests high to low flow regime of transportation; the inclusive graphic skewness shows positive skewness with few samples falling under negative skewness ranging from −0.1 to 2.0; the inclusive graphic standard deviation ranges from 1.0 to 1.4; and the inclusive graphic kurtosis ranges from 0.68 to 4. The probability plot of the representative rock samples shows that the Bima Sandstone was transported by saltation and suspension, while the bivariate scatter plot of Y2 against Y3 suggests that the Bima Sandstone is deposited in a continental setting.